Relationship between executive functions and physical activity level in secondary-high school students (Agora for Physical Education and Sport, 2020)
The objective of this work was to know the relationship between the level of physical activity and executive functions (cognitive flexibility and inhibition); and the differences according to gender, age and type of sport practiced in students aged between 12 and 17 years old. The research sample consisted of 71 students (28 boys and 43 girls). The level of physical activity was evaluated through the Physician-based Assessment and Counseling for Exercise, cognitive flexibility through the Design Fluency Test, and for the inhibitory mechanisms the Stroop Test was used. The results of this work showed that there is a positive and significant relationship between hours of physical activity and cognitive flexibility in adolescents. In terms of gender, boys obtained significantly higher values of hours of physical activity. In addition, older students had significantly higher scores on executive functions. Finally, the students of collective sports show significantly higher values of hours of physical activity practice and cognitive flexibility.
Keywords: sport; education; teenagers; cognitive flexibility; inhibition